2018
DOI: 10.1159/000493819
|View full text |Cite
|
Sign up to set email alerts
|

Omi/HtrA2 Regulates a Mitochondria-Dependent Apoptotic Pathway in a Murine Model of Septic Encephalopathy

Abstract: Background/Aims: the pathogenesis of sepsis-associated encephalopathy (SAE) is multifactorial, involving neurotransmitter alterations, inflammatory cytokines, oxidative damage, mitochondrial dysfunction, apoptosis, and other factors. Mitochondria are major producers of reactive oxygen species, resulting in cellular injury. Omi/HtrA2 is a proapoptotic mitochondrial serine protease involved in caspase-dependent cell death; it is translocated from mitochondria to the cytosol after an apoptotic insult. We previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 23 publications
(31 reference statements)
0
21
0
Order By: Relevance
“…Also, statin drugs inhibit the prenylation of Rac and Rho proteins [36], upgrading the expression of endothelium-derived nitric oxide synthetase (eNOS). In turn, eNOS increases NO expression, maintaining endothelial cell function, attenuating BBB damage in sepsis patients [37], thereby reducing the rate of SAE among sepsis patients through an antiin ammatory pathway. However, the exact pharmacological mechanism of immunomodulation caused by statins has not clearly been demonstrated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Also, statin drugs inhibit the prenylation of Rac and Rho proteins [36], upgrading the expression of endothelium-derived nitric oxide synthetase (eNOS). In turn, eNOS increases NO expression, maintaining endothelial cell function, attenuating BBB damage in sepsis patients [37], thereby reducing the rate of SAE among sepsis patients through an antiin ammatory pathway. However, the exact pharmacological mechanism of immunomodulation caused by statins has not clearly been demonstrated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary inflammation has always been a characteristic of pneumonia ( 14 ). Although UCF-101 has been indicated to be anti-inflammatory in the pathogenesis of sepsis complications and colitis ( 8 , 9 , 15 ), the special anti-inflammatory role of UCF-101 in pneumonia remains to be elucidated. Consistent with the reported studies that UCF-101 suppressed the release of pro-inflammatory cytokines such as TNF-α, IL-6 and IL-1β in colon tissue in colitis, UCF-101 also decreased the levels of TNF-α, IL-6, IL-1β and MCP-1 in LPS-induced pneumonia rats in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…UCF-101 was found to suppress the protease activity of HtrA2 to reduce caspase-independent apoptosis ( 24 ). Wang et al ( 15 ) reported that mitochondrial HtrA2 expression is reduced in murine sepsis, together with a translocation of HtrA2 from mitochondria to the cytoplasm, while UCF-101 blocks the mobilization of HtrA2 from mitochondria to the cytoplasm, and reduces XIAP, cleaved caspase-3 and caspase-9 to alleviate sepsis-associated encephalopathy. Hu et al ( 9 ) demonstrated the neuroprotective effect of UCF-101 by inhibiting caspase activity and cell apoptosis to attenuate sepsis-induced cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations of SAE vary greatly, from compromise in attention and orientation to delirium and even coma (5). Neuronal apoptosis, microcirculatory dysfunction and mitochondrial dysfunction has been implicated in SAE (6)(7)(8). The local production of pro-in ammatory mediators may resulting in impairment of central nervous system, and thus, microglia activation and the release of in ammatory cytokines, such as TNF-α and IL-1β, play a central role in the development of SAE (9,10).…”
Section: Introductionmentioning
confidence: 99%